The Evaluation of Countercyclical Policy Implementation in Facing the Impact of the Spread of COVID-19 (Study on Central Kalimantan Bank Pension Fund) - Ike Trisia (Budapest International Research and Critics University, 2020)
This research is a qualitative descriptive study that aims to determine the implementation of countercyclical policies that have been implemented by the Central Kalimantan Bank Pension Fund in dealing with the impact of the spread of COVID-19. The data processed in this study were obtained using interview techniques and supplemented with secondary data which was accessed from various sources. The results of this study indicate that the Bank Kalteng Pension Fund has implemented the provisions of the countercyclical policy as in the Financial Services Authority Circular Letter Number S-10 / D.05 / 2020. In implementing the countercyclical policy, the Bank Kalteng Pension Fund implements the Relaxation of Periodic Report Submission, Implementation of Fit and Proper Tests through Video Converence and Investment Shift to Low Risk Investments.